Pengaruh Pemberian Nesting Terhadap Kualitas Tidur pada Bayi Prematur : A Literature Review - Riyantika Ayu Ramandhani; Meira Erawati (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2021)
Preterm infant’s condition is a major risk factor for increased morbidity and mortality rate. Preterm infants that getting treatment in the neonatal intensive care unit (NICU) will be disrupted due to different factors that causing sleep distrubance on the infant. Due to the critical role of sleep in premature infant’s brain development, that developmental care as nesting is needed to facilitate sleep’s necessary. This study aimed to explore the implication of nesting on sleep quality’s preterm infants in the NICU. Method of research was literatur review study. Articles were collected from several databases including Google Scholar, PubMed, JSTOR, and ScienceDirect. The keywords were preterm infant, nesting, and sleep were searched for original studies. The articles reviewed were indexed article in Scopus and published during period 2010 to 2020. It found 7 articles that related specifically to effect of nesting on sleep quality and period’s preterm infants. The implementation of nesting as developmental care strategy can be combined with other intervention methods such as nesting-swaddling, nesting-variation of positioning, and the use of new nest model. Nesting methods affect the duration of sleep in the active sleep, quiet sleep, and the transitional sleep status. Applying nesting as a developmental care is able to increase duration of sleep on active sleep, quiet sleep, and transitional sleep status.